New Leadership Imperatives Inspiring the next game : strategy ideas for forward looking leaders. - Reeves, Martin; Candelon, François (Inspiring the next game (Series), 2022)
Leaders and their organizations do not operate in a vacuum but both influence and are influenced by the environment. Today's business organizations are fast moving, uncertain, politicized, sustainability challenged and technologically fluid. This business climate requires new approaches to leadership. Some leaders will rise to the occasion, while others will struggle to adapt. New Leadership Imperatives explores the new challenges of leadership and discusses how leaders can help their organizations to successfully adapt to new conditions. Drawing on lessons from various fields--from military to sports to psychology and neuroscience--this book delves into the challenges leaders face, ranging from social polarization to geopolitical instability. This book aims to guide leaders in making the right choices for their teams, their organizations, their stakeholders, and society as a whole.